Metalloproteinases in metabolic syndrome - Berg, Gabriela Alicia (2011)
Experimental and clinical evidence supports the concept that metalloproteinases (MMPs), beyond different physiologic functions, also play a role in the development and rupture of the atherosclerotic plaque. Interest in MMPs has been rapidly increasing during the last years, especially as they have been proposed as biomarkers of vulnerable plaques. Different components of the metabolic syndrome (MS) have been identified as possible stimulus for the synthesis and activity of MMPs, like pro-inflammatory and pro-oxidant state, hyperglycemia, hypertension and dyslipidemia. On the other hand, anti-inflammatory cytokines like adiponectin are inversely associated with MMPs. Among the several MMPs studied, collagenases (MMP-1 and MMP-8) and gelatinases (MMP-2 and MMP-9) are the most associated with MS. Our aim was to summarize and discuss the relation between different components of the MS on MMPs, as well as the effect of the cluster of the metabolic alterations itself. It also highlights the necessity of further studies, in both animals and humans, to elucidate the function of novel MMPs identified, as well as the role of the known enzymes in different steps of metabolic diseases. Understanding the mechanisms of MS impact on MMPs and vice versa is an interesting area of research that will positively enhance our understanding of the complexity of MS and atherosclerosis.